Exploring the Prevalence and Factors Associated With Fatigue in Axial Spondyloarthritis in an Asian Cohort in Singapore - Lim, Wei Ze; Fong, Warren; Kwan, Yu Heng; Leung, Ying Ying (Frontiers in Medicine, 2021)
Aim: To evaluate the prevalence of fatigue and the factors associated with fatigue among patients with axial spondyloarthritis (axSpA) within an Asian population. Method: We used the baseline data from a clinic registry in a tertiary referral centre. All patients fulfilled the 2009 Assessment of SpondyloArthritis international Society (ASAS) classification criteria for axSpA. Severe fatigue was defined as Bath Ankylosing Spondylitis Disease Activity Index-fatigue (BASDAI-fatigue) ≥ 5/10 and vitality domain of Short Form-36 Health Survey (SF-36 VT) ≤ 10th percentile of the general population. Results: We included 262 consecutive patients with axSpA (79% men, 82.4% Chinese). The mean (standard deviation, SD) age and duration of disease were 41.7 (13.7) and 10.1 (8.3) years respectively. 145 (55.3%) and 52 (31.1%) patients reported severe fatigue by the BASDAI-fatigue and SF-36 VT criteria respectively. Patients with severe fatigue had worse scores across all disease activity assessments and disease impact measures compared to those without severe fatigue. Using principal component analyses, disease activity and impact were associated with BASDAI-fatigue, while disease activity and impact, and disease chronicity were associated with SF-36 VT. In the univariable analyses, all disease activity assessments and disease impact measures correlated with both BASDAI-fatigue and SF-36 VT. In the multivariable analyses, BASDAI-axial pain, BASFI, BAS-G and ethnicity were associated with BASDAI-fatigue, while ASQoL and BASDAI-morning stiffness were associated with SF-36 VT. Conclusion: Fatigue is prevalent amongst patients with axSpA in Asia and is associated with disease activity, disease impact as well as patient related factors.